Caffeine regulates both osteoclast and osteoblast differentiation via the AKT, NF-κB, and MAPK pathways - Miao, Yue; Zhao, Lei; Lei, Shuwen; Zhao, Chunyan; Wang, Qiuping; Tan, Chao; Peng, Chunxiu; Gong, Jiashun (Frontiers in Pharmacology, 2024)
While caffeine generally offers benefits to human health, its impact on bone metabolism remains unclear. This study aimed to systematically evaluate the long-term effects of caffeine administration on osteoclasts, osteoblasts, and ovariectomy-induced postmenopausal osteoporosis. Our in vitro findings revealed that 3.125 and 12.5 μg/mL caffeine inhibited RANKL-mediated osteoclastogenesis in RAW264.7 cells though the MAPK and NF-κB pathways, accompanied by the inactivation of nuclear translocation of nuclear factor of NFATc1. Similarly, 3.125 and 12.5 μg/mL caffeine modulated MC3T3-E1 osteogenesis via the Akt, MAPK, and NF-κB pathways. However, 50 μg/mL caffeine promoted the phosphorylation of IκBα, P65, JNK, P38, and AKT, followed by the activation of NFATc1, inactivation of Runx2 and Osterix, ultimately disrupting the balance between osteoblastogenesis and osteoclastogenesis. In vivo, studies showed that gavaged 55.44 mg/kg caffeine inhibited osteoclastogenesis, promoted osteogenesis and ameliorated bone loss in ovariectomized mice. Conversely, long-term intake of high-dose caffeine (110.88 mg/kg) disrupted osteogenesis activity and promoted osteoclastogenesis, thereby disturbing bone homeostasis. Collectively, these findings suggest thata moderate caffeine intake (approximately 400 mg in humans) can regulate bone homeostasis by influencing both osteoclasts and osteoblasts. However, long-term high-dose caffeine consumption (approximately 800 mg in humans) could have detrimental effects on the skeletal system.